Prevalence and molecular characterization of glucose-6-phosphate dehydrogenase deficiency in Northern Thailand - Pimlak Charoenkwan (2018)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is one of the most common inherited enzymopathies in endemic areas of malaria including Southeast Asia. The molecular features of G6PD deficiency are similar among Southeast Asian population, with differences in the type of the prominent variants in each region. This study determined the prevalence and molecular characteristics of G6PD deficiency in northern Thailand. Quantitative assay of G6PD activity was conducted in 566 neonatal cord blood samples and 6 common G6PD mutations were determined by PCR-restriction fragment length polymorphism method on G6PD complete and intermediate deficiency samples. Ninety newborns had G6PD deficiency, with prevalence in male newborns of 17% and that of female newborns having an intermediate and complete deficiency of 13% and 2%, respectively. From 95 G6PD alleles tested, G6PD Mahidol, G6PD Kaiping, G6PD Canton, G6PD Viangchan, G6PD Union, and G6PD Chinese-5 was detected in 19, 17, 15, 13, 7, and 2 alleles, respectively. Our study shows that the prevalence of G6PD deficiency in northern Thai population is high and combination of the common Chinese mutations is the majority, a distribution different from central and southern Thailand where G6PD Viangchan is the prominent variant. These findings suggest a higher proportion of assimilated Chinese ethnic group in the northern Thai population.